Nucleotide sequences for the gene junctions of human respiratory syncytial virus reveal distinctive features of intergenic structure and gene order. - Collins, P L (1986)
Complete sequences for the intergenic regions of the genome of human respiratory syncytial virus were obtained by dideoxynucleotide sequencing using synthetic oligonucleotides. These experiments established that the 10 respiratory syncytial viral genes are arranged, without additional intervening genes, in the order 3' 1C-1B-N-P-M-1A-G-F-22K-L 5'. For the first nine genes, the exact gene boundaries were identified by comparison of the genomic sequences with previously determined mRNA sequences. The intergenic regions varied in length from 1 to 52 nucleotides and lacked any obvious conserved features of primary or secondary structure except that each sequence ended (3' to 5') with an adenosine residue. The exact start site of the 10th gene, the L gene, was not determined. However, RNA blot hybridization using a synthetic oligonucleotide designed from the genomic sequence mapped the L gene to within 54 nucleotides of the end of the penultimate 22K gene. The lack of conservation of chain length and nucleotide sequence for the respiratory syncytial viral intergenic regions, together with the complexity of the genetic map, contrasts with previous observations for other nonsegmented negative-strand viruses.